Consumer Legal Protection Against Service Non-Conformity in the Organization of Music Concerts in Indonesia - Geisya Safana Camila; Rois Harliyanto (Ridwan Institute, 2026)
The increase in concert organizing in Indonesia in recent years has had a positive impact on the economy. However, the organization of music concerts also causes consumer losses due to the incompatibility of services promised by the event organizers. This research aims to analyze the types of defaults and forms of consumer legal protection against service inconsistencies in the implementation of music concerts. The method used in this study was normative juridical with a statutory approach, a conceptual approach, and an analytical approach focused on the provisions of the Civil Code and Law Number 8 of 1999 concerning Consumer Protection (UUPK). The results of this study found that unilateral cancellation of events without a clear reason, change of location after tickets are sold, rescheduling, and implementation that is not in accordance with the agreement are forms of default in the entertainment services sector. This creates a legal responsibility for the organizer to provide compensation. Consumer legal protection is also provided preventively and repressively. Although it has been regulated normatively, its implementation is still not optimal, so it is necessary to strengthen regulations and legal implementation in the field of entertainment services